Desempenho das organizações paraibanas do terceiro setor: um estudo à luz das estratégias de governança - Queiroz, Daniel Ferreira de (2024)
For the purpose of guarantee satisfactory organizational performance, the institutions that compose the Third Sector need to develop governance strategies, aiming, above all, to meet the needs of their stakeholders. From this context emerges the practice of accountability, whose concept is related to the responsibility of accounting for the actions developed to the various stakeholders, in a way that allows them to evaluate organizational performance based on the data and information made available. Given the above, this study aims to verify how governance strategies, based on accountability, affect organizational performance in Third Sector Entities in the State of Paraíba. The theoretical framework addresses relevant characteristics about the Third Sector, also listing strategies that strengthen the governance process in these organizations. To this end, we sought input from stakeholder theory, which contributes to elucidating the relationships that an organization has with the most varied interested parties, what enhances its organizational performance. This research, with a qualitative approach, has a descriptive nature, being developed in two stages. In order to identify entities with potential to contribute to elucidating the research problem, in the first stage, a mapping of Third Sector Organizations was carried out in the various municipalities of the State of Paraíba, stratified by each mesoregion. Subsequently, an online form was applied to institutions located in the city that, in each of the mesoregions, hosted the largest number of these organizations. For the development of the second stage, 04 organizations were delimited, located in the different mesoregions of the State, with the data collection procedure, in addition to document analysis, carrying out a semi-structured interview, whose data were triangulated and analyzed. The results highlighted, firstly, the relevant role played by the third sector in the State of Paraíba, whose organizations operate mainly through the defense of social rights. It was also observed that the governance structure model adopted complies with the recommendations of the Brazilian Civil Code, privileging aspects such as decentralization in the decision-making process, as well as the need for collective action between the various administrative bodies. It was also identified that the largest source of resources comes from the public administration, with a unanimous conception regarding the need for accountability, as well as a wide dissemination of the results achieved with its various stakeholders, a process that, according to with the interviewees, will result in greater reliability, as well as increased revenue. It was finally evidenced that visibility before granting bodies, as well as other stakeholders, in addition to the openness of governance structures to accommodate their demands, as well as planning, monitoring and evaluation strategies, are characterized as key elements that could assist in the accountability process and, therefore, organizational performance. By carrying out this research, the relevance of stakeholder theory is made clear in terms of strengthening accountability processes, which prove to be extremely effective when applied in Third Sector Organizations, in view of satisfactory organizational performance.